2020
DOI: 10.1002/cpdd.894
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Steroidogenic Exposure Following the Administration of Repository Corticotropin Injection With a Synthetic ACTH1‐24 Depot and Methylprednisolone in Healthy Subjects

Abstract: The pharmacokinetics (PK) and pharmacodynamics (PD) of clinically relevant doses of repository corticotropin injection (Acthar Gel) and synthetic ACTH1‐24 depot have not been fully characterized. We compared the steroidogenic exposure of repository corticotropin injection and synthetic ACTH1‐24 depot in healthy adults at therapeutic doses using data from 2 separate phase 1 studies. Subjects were randomly assigned to repository corticotropin injection 40 or 80 IU subcutaneously twice weekly or 80 IU subcutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Synthetic ACTH 1‐24 depot is an investigational drug that is similar to Synacthen Depot, a product used therapeutically in other countries. Results of previous studies have suggested that RCI has less functional activity at MC2R 23 and induces a lower level of endogenous cortisol production than synthetic ACTH 1‐24 depot after a single dose 26,27 . An indirect comparison of 2 independent pharmacokinetic (PK) and pharmacodynamic (PD) studies of RCI and synthetic ACTH 1‐24 depot used a model‐based simulation to compare clinically relevant doses of each drug and found that RCI induced lower cortisol exposure and had a lower steroidogenic exposure than synthetic ACTH 1‐24 depot 27 .…”
mentioning
confidence: 99%
“…Synthetic ACTH 1‐24 depot is an investigational drug that is similar to Synacthen Depot, a product used therapeutically in other countries. Results of previous studies have suggested that RCI has less functional activity at MC2R 23 and induces a lower level of endogenous cortisol production than synthetic ACTH 1‐24 depot after a single dose 26,27 . An indirect comparison of 2 independent pharmacokinetic (PK) and pharmacodynamic (PD) studies of RCI and synthetic ACTH 1‐24 depot used a model‐based simulation to compare clinically relevant doses of each drug and found that RCI induced lower cortisol exposure and had a lower steroidogenic exposure than synthetic ACTH 1‐24 depot 27 .…”
mentioning
confidence: 99%
“…These data suggest that RCI may improve SLErelated QoL and impairments beyond the improvements provided by background glucocorticoid and other standard-of-care treatments. Notably, previous studies have demonstrated that RCI induces an endogenous cortisol response that is comparable to low-to-moderate daily glucocorticoid doses [30]; thus, the use of RCI instead of increasing glucocorticoid doses in persistently active disease may be advantageous for reducing steroid exposure while still providing clinical benefit. Additionally, these data suggest that RCI may have greater benefit in patients with higher disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, in animal studies, RCI induced significantly lower corticosterone levels than synthetic ACTH 1–24 , consistent with their respective functional activity at MC2R [ 28 ]. Pharmacologic studies in healthy human subjects have also demonstrated that RCI induces lower cortisol production than does synthetic ACTH 1–24 depot at clinically relevant doses, further supporting that RCI has a unique mechanism of action [ 30 , 31 ]. The lower cortisol response of RCI was achieved despite plasma concentrations of the pharmacokinetic marker of RCI (N25-deamidated porcine ACTH 1–39 ) being higher than concentrations of ACTH 1–24 [ 31 ].…”
Section: Introductionmentioning
confidence: 99%